Manhaj Muqtarah Li Ta’lîmi Al-Lughah Al-Arabiyyah Al-Jawiyyin Al-Mubtadiîn Bi Istikhdâmi Al-Kalimât Dzâti An-Nadhôir Al-Mukhôdiah Fi Qômus (Bahasa Jawa-Indonesia) Min Harfi A-F Namûdzajan - Nurul Innayati (Mauriduna: Journal of Islamic Studies, 2020)
وجود الكلمات الجاوية ذات النظائر المخادعة يكون تيسيرا للمبتدئين الجاويين في التعليم اللغة العربية لأن ظهر فيها تشابه الكلمات بين اللغة العربية واللغة الجاوية، ومهما كان لها الاختلاف في معنى، وكذا وجود المعاهد الكثيرة والمنتشرة في جزيرة الجاوي بيان بأن اللغة العربية محبوبة عندهم. ومن هنا قبل أن يبدأ المعلم بتعليم اللغة العربية يحتاج المعلم إلى بناء منهج مقترح تعليمي لتنظيمي الفصل حقا تنظيما لتحقيق الأهداف المخططة والواضحة المدرسية العامة والخاصة وموافق التعلم. من هذه الأشياء هدفت الباحثة بناء منهج مقترح لتعليم اللغة العربية الجاويين المبتدئين باستخدام النظائر المخادعة في قاموس اللغة الجاوية الشامل لسودرمانتو من حرفA إلى F ، ترغيبا وسهولة لهم في تعليم هذه اللغة الثانية وهي اللغة العربية ومنهج الذي سلكت الباحثة لكتابة هذا البحث هو منهج وصف تحليلي. ولبناء منهج تعليم استخدمت الباحثة الكلمات ذات النظائر المخادعة في 3 النماذج الأساسية وهي: الصور والحوار والنصوص التي وضعت مع مراعاة عناصر اللغة الثلاثة وهي: المفردات والأصوات والتراكيب وكذا مراعاة عناصر منهج تعليمي وهي: الأهداف، المحتويات، عروض الدروس ،الوسائل التعليمية، والتقويمات. The existence of Javanese words that have homonyms with Arabic supports beginners in learning Arabic due to the similarity of words appearing between Arabic and Javanese despite differences in meaning, and the presence of many Islamic boarding schools and Islamic institutions scattered on the island of Java proves that Arabic is loved by them. Therefore, before teachers begin teaching Arabic, teachers need to develop a suggested educational approach for classroom organizations, which are truly operationalized to achieve clearly planned goals of public and private schools and learning competitions. Among these things, researchers aim to build a proposed curriculum for teaching Arabic beginners, using homonyms between Arabic and Javanese in the complete Javanese dictionary Sodermanto from letters A to F. This gives their love and ease in teaching this second language, which is Arabic, the ambitious curriculum for writing this research is the analytical description method. To build an educational curriculum, and apply these words in 3 basic models: pictures, dialogues and texts developed based on three elements of language: vocabulary, sounds, and composition, and take into account elements of the educational curriculum: objectives, content, lesson presentation, teaching aids, and exercises.